1976
DOI: 10.1364/ao.15.002701
|View full text |Cite
|
Sign up to set email alerts
|

Vibration phase mapping using electronic speckle pattern interferometry

Abstract: The contours of constant phases across sinusoidally vibrating objects have been mapped using reference wave phase modulation in time-average electronic speckle pattern interferometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(21 citation statements)
references
References 5 publications
0
20
0
1
Order By: Relevance
“…For these reasons most detailed descriptions of the motion of the mammalian TM were obtained by means of time-averaged holograms Lokberg and Hogmonen, 1976;Tonndorf and Khanna, 1972;Wada et al, 2002). Time-averaged holography and holographic interferometry enable to record the complete vibration pattern of a surface within several seconds (Dancer et al, 1975;Khanna and Tonndorf, 1972;Saldner, 1996;Tonndorf and Khanna, 1972).…”
Section: Vibration Response and Displacement Measurementsmentioning
confidence: 99%
“…For these reasons most detailed descriptions of the motion of the mammalian TM were obtained by means of time-averaged holograms Lokberg and Hogmonen, 1976;Tonndorf and Khanna, 1972;Wada et al, 2002). Time-averaged holography and holographic interferometry enable to record the complete vibration pattern of a surface within several seconds (Dancer et al, 1975;Khanna and Tonndorf, 1972;Saldner, 1996;Tonndorf and Khanna, 1972).…”
Section: Vibration Response and Displacement Measurementsmentioning
confidence: 99%
“…The intensity distribution of a sinusoidally vibrating object with a frequency much higher than the video frame rate as [5][6][7][8][9][10][11][12] …”
Section: Time Average Fringe Analysismentioning
confidence: 99%
“…TV holography (TVH) is a well established optical tool for the measurement deformation under static as well as dynamic load on rough surfaces [1][2][3][4]. Recent studies have demonstrated promising complementary approaches for the vibration fringe analysis using TV holography with the continuous and the stroboscopic illumination which provide the time-average [5][6][7][8][9][10][11][12] or the time-resolved [13][14][15][16] respectively of the object vibration modes under harmonic excitation at resonant frequencies. Time-averaged method is the most frequently used technique for full-field vibration analysis of harmonically excited components because the optoelectronic setup is same as the static one.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is not exploited straightforwardly for the determination of the local mechanical phase of an object in sinusoidal motion unless if a high framerate sensor is used [4]. A stroboscopic approach can alleviate this issue.Several holographic and interferometric approaches have been proposed and validated for mechanical phase retrieval from sequences of intensity images under phase-stepped stroboscopic illumination [7][8][9][10].In this letter, we report the use of a stroboscopic scheme in conjunction with frequency-shifted modulation sideband detection to map mechanical phase shifts with respect to the excitation signal at a given vibration frequency. Detuning the strobe frequency with respect to the mechanical excitation signal by a fraction of the sampling frequency can be used to freeze m linearly-spaced vibration states over a vibration period.…”
mentioning
confidence: 99%